49.6k views
4 votes
NO LINKS!! Please help me with this problem​

NO LINKS!! Please help me with this problem​-example-1
User Nekeniehl
by
5.7k points

2 Answers

5 votes


{\qquad\qquad\huge\underline{{\sf Answer}}}

The given vertex and Focus are of a vertical parabola having an opening downward as the focus is in downward direction as the vertex.

Focus of the parabola can be written as :


\qquad \sf  \dashrightarrow \: (h ,k+ a )

where, h and k are coordinates of vertex

so,

  • k + a = -2

  • -1 + a = -2

  • a = -1

So, the equation of parabola can be written as :


\qquad \sf  \dashrightarrow \: (x - h) {}^(2) = 4a(y - k)

plug in the values ~


\qquad \sf  \dashrightarrow \: (x - 1) {}^(2) = 4(- 1)(y + 1) {}^{}


\qquad \sf  \dashrightarrow \: (x - 1) {}^(2) = - 4(y + 1)

User Pedromtavares
by
4.6k points
1 vote

Answer:


(x-1)^2=-4(y+1)

Explanation:

Standard form of a parabola with a vertical axis of symmetry:


(x-h)^2=4p(y-k) \quad \textsf{where}\:p\\eq 0

  • Vertex = (h, k)
  • Focus = (h, k+p)
  • Directrix: y = (k-p)
  • Axis of symmetry: h = k
  • If p > 0, the parabola opens upwards, and if p < 0, the parabola opens downwards.

Given:

  • vertex = (1, -1)
  • focus = (1, -2)

Comparing with the formulas:

⇒ h = 1

⇒ k = -1

⇒ k + p = -2 ⇒ -1 + p = -2 ⇒ p = -1

Substituting the values into the formula:


\implies (x-1)^2=4(-1)(y-(-1))


\implies (x-1)^2=-4(y+1)

User Executifs
by
4.0k points